Overcoming barriers to knowledge co-production in academic–practitioner research collaboration. Issue 2 (April 2023) - McCabe, Angela; Parker, Rachel; Osegowitsch, Tom; Cox, Stephen
Abstract: Knowledge co-production involving collaborating academics and practitioners is a recognized vehicle for stimulating innovation. However, co-production is hampered by a number of significant barriers, including structural differences between the partners, the mismanagement of conflict, and a traditional outlook on knowledge. We explore academic-practitioner research collaborations to document the specific practices allowing collaborators to address co-production barriers. The primary data for this study were collected from semi-structured interviews with academics and practitioners working on 24 Australian Research Council (ARC) Linkage projects. The main contribution of this investigation is the identification of 'academic cultivation' in overcoming barriers to knowledge co-production. Academic cultivation denotes a situation where practitioner behavior designed to overcome one or other of the co-production barriers is prompted through prior actions by the academic.